Itsbat Nikah dalam Perspektif Undang-Undang Perkawinan dan Kompilasi Hukum Islam ( KHI): Studi Perbandingan Putusan No. 87/Pdt.P/2025/Pa Spn dan No. 165/Pdt.P/2025/Pa Spn di Pengadilan Agama Sungai Penuh - Erivan Angga Utama; Widiya Yul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study is entitled “Itsbat Nikah in the Perspective of the Marriage Law and the Compilation of Islamic Law (KHI): A Comparative Study of Decision No. 87/Pdt.P/2025/PA.Spn and No. 165/Pdt.P/2025/PA.Spn at the Sungai Penuh Religious Court.” The research aims to analyze and compare the judges’ legal reasoning in two itsbat nikah cases that resulted in different decisions, as well as to evaluate the application of legal norms from the perspective of the Marriage Law and the Compilation of Islamic Law (KHI). The research employs a normative–juridical approach (doctrinal legal research) combined with comparative and qualitative methods. The normative approach is used to examine written legal norms, such as Law No. 1 of 1974 in conjunction with Law No. 16 of 2019 and the KHI, as well as their implementation in the practice of religious courts. The comparative approach identifies similarities, differences, and patterns of judicial interpretation between the two decisions, while the qualitative approach interprets the meaning behind the judges’ legal considerations in a descriptive and interpretative manner. The findings indicate that the judges of the Sungai Penuh Religious Court applied the principle of harmonization between Islamic law and Indonesian positive law in assessing the validity of unregistered marriages. Decision No. 87/Pdt.P/2025/PA.Spn reflects an administrative-sociological approach, emphasizing the principle of maslahah and the community’s administrative needs to obtain legal certainty for religiously valid marriages. In contrast, Decision No. 165/Pdt.P/2025/PA.Spn demonstrates a normative-restrictive approach, rejecting the itsbat nikah petition due to a violation of the minimum marriage age as stipulated in Article 7 paragraph (1) of Law No. 16 of 2019. This difference shows that itsbat nikah is not merely a mechanism for legalizing unregistered marriages, but a judicial instrument to uphold legal certainty in line with justice, public benefit, and human rights protection. Accordingly, this study underscores the importance of synergy between religious law and state law in developing a fair, adaptive, and socially protective marriage legal system.